Organic-inorganic hybrid polymer hydrogel, preparation method thereof and exterior wall thermal insulation mid-coat paint
By using organic-inorganic hybrid polymer hydrogels and modified hollow glass microbeads in exterior wall insulation coatings, the problems of insufficient brittleness and hydrophobicity of silica aerogels are solved, and the coating has high water resistance, low thermal conductivity and stability are achieved.
Patent Information
- Application Number
- CN202211647485.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-21
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-12-21
AI Technical Summary
Among the existing exterior wall insulation coatings, the silica aerogel is insufficient in brittleness and hydrophobicity, resulting in poor toughness and mechanical strength of the coating, and poor compatibility with acrylic resin emulsions, affecting the stability and performance of the coating.
Using organic-inorganic hybrid polymer hydrogel, the spatial network structure is formed by crosslinking silica inorganic nanoparticles and bridged polymers, and hydrophobicity is enhanced, and the adhesion and water resistance of the coating are enhanced by combining modified hollow glass microbeads.
The excellent water resistance of the coating, substrate adhesion and low thermal conductivity of the coating are achieved, which enhances the stability and performance of the coating, and avoids the problems of coating agglomeration and excessive viscosity.
Smart Images

Figure GDF0000035406630000021 
Figure GDF0000035406630000031 
Figure GDF0000035406630000041
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of architectural coatings, and more specifically to an organic-inorganic hybrid polymer hydrogel, a preparation method thereof and an exterior wall thermal insulation mid-coat. Background Art
[0002] Reducing building energy consumption is a social problem that needs to be solved urgently under the requirements of low carbon. Using thermal insulation materials for building exterior walls is one of the effective methods. Traditional exterior wall thermal insulation materials mainly include polystyrene particle board plastering system, rock wool board system and thermal insulation decorative board system. However, this type of material has poor adhesion to the wall and poses a great safety risk. In recent years, accidents of exterior wall insulation layer falling off have occurred in various places, causing serious life safety hazards and property losses. Based on this, lightweight thermal insulation coatings continue to emerge on the market. At present, most lightweight thermal insulation coatings on the market mainly use two technical routes: Path one uses hollow glass microspheres as the main functional powder; Path two uses silica aerogel as the main functional powder.
[0003] For example, for technical path 1, CN 111410880A discloses an environmentally friendly heat-insulating middle-layer paint, including an upper-layer paint and a lower-layer paint, wherein the upper-layer paint uses titanium dioxide (20-40 parts) as the main functional powder to provide a good reflective effect; the lower-layer paint uses hollow glass microspheres (15-30 parts) as the main functional powder to achieve a good heat-insulating effect. However, the interaction between the hollow glass microspheres and the acrylic resin emulsion is weak without pretreatment, and the floating of the lightweight glass microspheres will cause the powder to float and the liquid to sink, and the appearance of the paint after opening the can is poor; in addition, the middle-layer paint provided by the invention is a thin-coated middle-layer paint, which has certain limitations in the heat-insulating effect.
[0004] For technical path 2, CN 113061375A discloses a thermal insulation coating, which uses aerogel (15-20 parts) and calcium sulfate whiskers (3-5 parts) as the main functional powders. The calcium sulfate whiskers reduce the brittleness of the aerogel and improve the toughness and mechanical strength of the coating. However, the unpretreated aerogel powder is light and hydrophobic, and the reaction between it and surfactants such as acrylic resin emulsion is not ideal. It is directly added to the formula to cause a relatively poor dispersion effect.
[0005] Similarly, for the second technical path, China's invention patent CN109913007B discloses a water-soluble silica aerogel exterior wall reflective heat insulation coating, which obtains water-soluble silica aerogel by modifying silica, greatly improving its dispersion effect. However, during the use of the exterior wall, it is easy to absorb water, causing the aerogel to produce capillary force, thereby destroying the porous structure, reducing the bonding strength of the middle layer, and causing the middle layer to be damaged or the coating to be hollow.
[0006] Therefore, how to optimize and modify the existing silica aerogel, enhance its hydrophobicity and compatibility with acrylic resin emulsion, so as to obtain an exterior wall insulation mid-coat with excellent water resistance, substrate adhesion, low thermal conductivity and other properties, is an urgent problem to be solved. Summary of the invention
[0007] In order to solve the above-mentioned defects, the present invention provides an organic-inorganic hybrid polymer hydrogel. The organic-inorganic hybrid polymer hydrogel has a spatial network structure and has the following structure (I):
[0008]
[0009] In formula (I), the crosslinking point P is an inorganic nanoparticle of silicon dioxide;
[0010] In the bridging polymer linking the crosslinking points, the repeating unit A is an alkyl group, m Expressed as -(CH2) m -, 1 <m<1000;
[0011] In the bridging polymer linking the crosslinking points, the repeating unit B is any one of propyl methacrylate with a silanol group, propyl acrylate with a silanol group, and an alkyl with a silanol group, and B n It is represented as a homopolymer of B, with a degree of polymerization of n, 1 <n<1000;
[0012] In the bridging polymer linking the crosslinking points, the repeating unit C is any one of vinyl diacrylate, vinyl methacrylate, and allyl acrylate, and C k It is represented as a homopolymer of C, with a degree of polymerization of k, 1 <k<1000。
[0013] The solid mass fraction of the organic-inorganic hybrid polymer hydrogel (residue after heating at 250°C for 1 hour) is 28-40%. When 1.0-1.5% of an alcohol ester film-forming aid is added to the organic-inorganic hybrid polymer hydrogel at room temperature, a continuous transparent paint film can be formed. The paint film is porous, has a volume solid content of >90%, a film hardness of more than H, a tensile strength of >20MPa, a contact angle of water on the paint film surface under standard conditions (25°C, one standard atmospheric pressure) of >170°, and a thermal conductivity of 0.04-0.08W / (m·K).
[0014] The present invention also provides a method for preparing the organic-inorganic hybrid polymer hydrogel, comprising the following steps:
[0015] Step 1) methyl orthosilicate, monomer A and monomer B are blended in a molar ratio of 1:1:1 to 1:2:2 to obtain a mixed solution No. 1, and the mixed solution No. 1 is stored in dry ice mixed with ethanol until the temperature of the mixed solution No. 1 drops below 0°C, the temperature is maintained, methanol is slowly added, and the mixture is stirred at a low speed for 10 min to 1 h to obtain a sol-formed mixed solution No. 1. The equation of the sol reaction is as follows (II), and the trimethoxy groups of methyl orthosilicate and monomers A and B are mutually condensed to generate silicon dioxide nanoparticles:
[0016]
[0017] Step 2) blending monomer C, initiator, and deionized water to obtain a blend liquid No. 2, wherein the weight fractions of the components in the blend liquid No. 2 are: 20% to 50% by weight of monomer C, 1% to 5% by weight of initiator, stirring the blend liquid No. 2 at a low speed, and adjusting the pH value of the system to 7.5 to 9.0 using sodium hydroxide or ammonia water to obtain a blend liquid No. 2;
[0018] 3) The temperature of the sol-gelled No. 1 blend solution is adjusted to 45-55° C., and the No. 2 blend solution is slowly added thereto, and the temperature is maintained with low-speed stirring and condensation reflux, and a free radical polymerization reaction begins to occur, and gelation begins at the same time, which lasts for 2-6 hours until the pH value of the system rises to above 7.0, to obtain a No. 3 blend solution that has completed polymerization and gelation. The equation of the free radical polymerization reaction is as follows (III):
[0019]
[0020] Step 4) dialyzing the No. 3 blend at least 3 times to remove excess free reaction monomers from the system. After the dialysis is completed, 10% to 20% by weight of deionized water is added, and condensed and refluxed at 80 to 85° C. for about 0.5 to 5 hours to remove excess alcohol solvent, and finally obtain the organic-inorganic hybrid polymer hydrogel.
[0021] Further, the monomer A is at least one of 1,6-bistrimethoxysilylhexane (CAS NO.87135-01-1) and 1,2-bistrimethoxysilylethane (CAS NO.18406-41-2);
[0022] The monomer B is at least one of 3-(trimethoxysilyl)propyl methacrylate (CAS NO.2530-85-0), 3-(trimethoxysilyl)propyl acrylate (CAS NO.4369-14-6), and vinyl trimethoxysilane (CAS NO.2768-02-7);
[0023] The monomer C is at least one of vinyl diacrylate (CAS NO. 2274-11-5), vinyl methacrylate (CAS NO. 4245-37-8), and allyl acrylate (CAS NO. 999-55-3).
[0024] Furthermore, the initiator is azobisisobutyronitrile.
[0025] Furthermore, in step 2), only physical blending is performed and no chemical reaction occurs.
[0026] Furthermore, in step 3), in the free radical polymerization reaction, the double bonds of the groups containing ethylene are opened, free radical polymerization occurs, and the chain length is increased by continuous addition polymerization. At the same time, the trimethoxyl groups of the excess monomer ethylene in step 1) are hydrolyzed to form silanols, which are no longer reactive.
[0027] Furthermore, in step 4), each dialysis lasts for 8 hours, and new dialysis fluid (i.e., deionized water) is replaced between two dialysis. The present invention also provides an exterior wall thermal insulation mid-coat paint, comprising the following components in parts by weight:
[0028] Modified hollow glass microspheres 8.0-20.0 parts by weight,
[0029] 30.0-70.0 parts by weight of the aforementioned organic-inorganic hybrid polymer hydrogel,
[0030] Pigments and fillers 10.0-30.0 parts by weight;
[0031] 0.5-2.0 parts by weight of film-forming aid;
[0032] Dispersant 0.1-1.0 parts by weight;
[0033] Wetting agent 0.1-1.0 parts by weight;
[0034] Defoaming agent 0.1-1.0 parts by weight;
[0035] Antifreeze agent 0.5-2.0 parts by weight;
[0036] Thickener 0.1-1.0 parts by weight;
[0037] 0.1-1.0 parts by weight of bactericidal and mildew-proof agent;
[0038] 0.1-1.0 parts by weight of a pH adjuster; and
[0039] Deionized water 20.0-40.0 parts by weight.
[0040] Furthermore, the modified hollow glass microspheres are hollow glass microspheres surface-treated with a silane coupling agent, with a particle size of 10-150 μm and a bulk density of 0.14±0.03 g / cm3 , floating rate ≥99%, bearing strength ≥6.8MPa, silicon dioxide content>99%, wall thickness is about 0.8~1.5um, and sphericity is greater than 0.9.
[0041] Furthermore, the silane coupling agent is at least one of 3-aminopropyltriethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane and a titanate coupling agent.
[0042] Preferably, the modified hollow glass microsphere is CROSFECT MB-1020, with a particle size distribution of about 30-125 μm and a bulk density of 0.11-0.13 g / cm 3 , floating rate is greater than 99.0%, and the pressure bearing strength is 500PSI.
[0043] Furthermore, the pigment filler is calcium carbonate;
[0044] Further, the film-forming aid is lauryl alcohol ester;
[0045] Furthermore, the main component of the dispersant is polyacrylic acid ammonium salt, such as SN-5027 provided by San Nopco.
[0046] Furthermore, the main component of the wetting agent is a non-ionic ethoxylate, such as EMULSOGEN LCN 070 provided by Clariant, with an HLB value of 13.
[0047] Furthermore, the defoamer is a polyether-modified mineral oil defoamer containing hydrophobic silica, such as SN-Defoamer 154 provided by San Nopco.
[0048] Furthermore, the antifreeze agent is propylene glycol.
[0049] Furthermore, the thickener is BENTONE DY CE provided by Hemingway-Deqian and NATROSOL 250HBR provided by Ashland, and the main components are bentonite and hydroxyethyl cellulose, respectively, with a weight ratio of 1:2.
[0050] Furthermore, the bactericide and mildew preventer is ACTICIDE MBS provided by Thor, the active ingredients of which are MIT and BIT, and ACTICIDE EPW, the active ingredients of which are carbendazim and OIT.
[0051] Furthermore, the main component of the pH regulator is 2-amino-2-methyl-1-propanol, such as AMP-95 provided by Dow Chemical.
[0052] The present invention further provides a method for preparing the exterior wall thermal insulation mid-coat, comprising the following steps:
[0053] Step S1: firstly add part of the thickener and half of the defoamer, all the film-forming aids, wetting agents, dispersants and pH regulators into deionized water, and disperse for 10-15 minutes at a peripheral linear speed of 10-15 m / s on a dispersion plate;
[0054] Step S2: adding all the modified hollow glass microspheres, organic-inorganic hybrid polymer hydrogel and pigments and fillers, increasing the speed of the dispersion disk, and dispersing for 15-20 minutes at a peripheral linear speed of 15-20 m / s;
[0055] Step S3: adding the remaining thickener, defoamer, antifreeze agent and bactericide and mildew preventer, and dispersing for 20-30 minutes at a peripheral linear speed of 10-15 m / s on the dispersion plate to obtain the exterior wall thermal insulation intermediate coating.
[0056] Beneficial effects of the present invention:
[0057] The exterior wall thermal insulation mid-coat paint of the present invention selects modified hollow glass microspheres and organic-inorganic hybrid polymer hydrogel as functional components.
[0058] First, unlike traditional thermal insulation coatings, the formula of the present invention no longer uses inorganic silica aerogel and organic film-forming substances (usually polymer acrylic emulsion / resin) alone, but hybridizes the two into an organic-inorganic hybrid dispersion (i.e., the organic-inorganic hybrid polymer hydrogel). When added to the coating, the dispersion effect and production efficiency can be greatly improved, avoiding the problems that may arise when mixing silica aerogel and polymer emulsion / resin in coating production, such as coating agglomeration, excessive viscosity, and post-thickening.
[0059] Second, after the silica aerogel and the organic polymer are hybridized, the overall hydrophobicity is further enhanced, avoiding the capillary force generated inside the ordinary aerogel and destroying the internal structure;
[0060] Third, after the hollow glass microspheres are modified by the silane coupling agent, the wettability between the hollow glass microspheres and the acrylic emulsion is improved. The organic functional groups produced by the treatment of the outer layer of the hollow glass microspheres produce a strong chemical bond with the acrylic emulsion. Therefore, the compatibility of the modified hollow glass microspheres and the acrylic emulsion is greatly improved. The prepared coating product is very stable, and there will be no stratification after storage, and the appearance is relatively normal.
[0061] Fourth, the main organic components in the film-forming system are acrylic resin and polyalkane resin, which have excellent compatibility and bonding with low thermal conductivity insulation fillers (for the present invention, specifically modified hollow glass microspheres in the formula), providing the paint film with excellent substrate adhesion, water resistance and flexibility. The organic-inorganic hybrid system ensures that the paint film is both rigid and flexible, and has excellent mechanical properties;
[0062] Fifth, after film formation, the organic-inorganic hybrid polymer hydrogel fills the spaces between the silica nanoparticles. Although the polymer occupies part of the silica vacancies compared to ordinary silica aerogel, the polymer itself has a larger free volume and can produce certain voids after film formation. The overall specific surface area is not significantly reduced, and it still has a low thermal conductivity effect.
[0063] The exterior wall thermal insulation intermediate coating of the present invention is used in combination with the existing emission thermal insulation series topcoat to further enhance the exterior wall thermal insulation effect. DETAILED DESCRIPTION
[0064] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.
[0065] The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, it is carried out according to the general international standards, conventional conditions, or according to the conditions recommended by the manufacturer. Unless otherwise defined or specified, all professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method and material similar or equivalent to the content described can be applied to the method of the present invention.
[0066] The raw materials or reagents used in each embodiment are as follows:
[0067] (1) In the preparation of organic-inorganic hybrid polymer hydrogels:
[0068] Methyl orthosilicate was provided by Aladdin, CAS No. 681-84-5, purity >98%;
[0069] Monomer A is 1,6-bistrimethoxysilylhexane (CAS NO.87135-01-1), provided by Admas, purity>95%;
[0070] Monomer B is 3-(trimethoxysilyl)propyl methacrylate (CAS NO. 2530-85-0), provided by Admas, purity > 98%;
[0071] Monomer C is vinyl methacrylate (CAS NO. 4245-37-8), provided by Admas, purity > 98%;
[0072] The initiator was azobisisobutyronitrile, provided by Admas with a purity of >98%.
[0073] (2) In the preparation of the middle layer paint for exterior wall insulation:
[0074] The hollow glass microspheres are CROSFECT MB-1020, with a particle size distribution of approximately 30-125 μm, a bulk density of 0.10-0.13 g / cm3, a floating rate greater than 99.0%, and a compressive strength of 500 PSI;
[0075] The heavy calcium in the pigment and filler is OM4 calcium carbonate provided by Omya;
[0076] Coal-forming aids: dodecyl esters provided by Eastman;
[0077] The dispersant is SN-5027 provided by San Nopco;
[0078] The wetting agent was EMULSOGEN LCN 070 provided by Clariant, with an HLB value of 13;
[0079] The defoamer was SN-Defoamer 154 provided by San Nopco;
[0080] The antifreeze agent is propylene glycol;
[0081] The thickeners are BENTONE DY CE provided by Hemingway-Deqian and NATROSOL 250HBR provided by Ashland, the main components of which are bentonite and hydroxyethyl cellulose, respectively, with a weight ratio of 1:2;
[0082] The pH adjuster was AMP-95 provided by Dow Chemical;
[0083] The fungicides and mildew inhibitors are ACTICIDE MBS and ACTICIDE EPW provided by Thor.
[0084] Example
[0085] Example 1
[0086] An organic-inorganic hybrid polymer hydrogel has a structural formula as shown in formula (I), a chain length of a repeating unit A of m=500-600, a bridging polymer linking crosslinking points, a repeating unit B of propyl methacrylate homopolymer with a polymerization degree n=200-400, and a repeating unit C of vinyl methacrylate homopolymer with a polymerization degree k=50-100; the solid mass fraction of the organic-inorganic hybrid polymer hydrogel is 33±1%, and the thermal conductivity after film formation is 0.06W / (m·K).
[0087] The preparation method of the above organic-inorganic hybrid polymer hydrogel is:
[0088] Step 1) methyl orthosilicate, monomer A and monomer B are blended in a molar ratio of 1:1:1 to obtain a mixed liquid No. 1, and stored in dry ice mixed with ethanol until the temperature of the mixed liquid No. 1 drops below 0° C., maintaining the temperature, slowly adding methanol, and stirring at a low speed for 1 hour to obtain a solubilized mixed liquid No. 1;
[0089] Step 2) Blending monomer C, initiator and deionized water to obtain blend liquid No. 2, wherein the weight fractions of the components in blend liquid No. 2 are: 30% by weight of monomer C, 2% by weight of initiator, stirring blend liquid No. 2 at a low speed, and adjusting the pH value of the system to 7.5-9.0 with sodium hydroxide or ammonia water to obtain pre-emulsified blend liquid No. 2;
[0090] Step 3) adjusting the temperature of the sol-gelled No. 1 blend to 45-55° C., and slowly adding the pre-emulsified No. 2 blend thereto, maintaining the temperature with low-speed stirring and condensing and refluxing, starting a free radical emulsion polymerization reaction, and starting gelation, and continuing for 6 hours until the pH value of the system rises to above 7.0, to obtain a No. 3 blend that has completed polymerization and gelation;
[0091] Step 4) dialyze the No. 3 blend at least 3 times, each dialysis time is 8 hours, and new dialysis fluid (i.e., deionized water) is replaced between two dialysis. After the dialysis is completed, 20% by weight of deionized water is added, and condensation reflux is carried out at 80-85° C. for about 2 hours to finally obtain an organic-inorganic hybrid polymer hydrogel.
[0092] A thermal insulation mid-coat for exterior walls comprises the following components in parts by weight: 18.0 parts by weight of modified hollow glass microspheres, 40.0 parts by weight of organic-inorganic hybrid polymer hydrogel, 15.0 parts by weight of pigments and fillers, 1.0 parts by weight of film-forming aids, 0.5 parts by weight of dispersants, 0.3 parts by weight of wetting agents, 0.5 parts by weight of defoaming agents, 1.2 parts by weight of antifreeze agents, 0.4 parts by weight of thickeners, 0.2 parts by weight of pH regulators, 0.7 parts by weight of bactericides and mildew inhibitors, and 22.2 parts by weight of deionized water.
[0093] The preparation method of the above-mentioned exterior wall thermal insulation mid-coat comprises the following steps:
[0094] Step S1: firstly add part of the thickener and half of the defoamer, all the film-forming aids, wetting agents, dispersants and pH regulators into deionized water, and disperse for 10-15 minutes at a peripheral linear speed of 10-15 m / s on a dispersion plate;
[0095] Step S2: adding all the modified hollow glass microspheres, film-forming silica aerogel slurry and pigments and fillers, increasing the speed of the dispersion disk, and dispersing for 15-20 minutes at a peripheral linear speed of 15-20 m / s;
[0096] Step S3: adding the remaining thickener, defoamer, antifreeze agent and bactericide and mildew preventer, and dispersing for 20-30 minutes at a peripheral linear speed of 10-15 m / s on the dispersion plate to obtain the exterior wall thermal insulation intermediate coating.
[0097] Example 2
[0098] An organic-inorganic hybrid polymer hydrogel has a structural formula as shown in formula (I), a chain length of a repeating unit A of m=600-700, a bridging polymer linking crosslinking points, a repeating unit B of propyl methacrylate homopolymer with a polymerization degree n=400-500, and a repeating unit C of vinyl methacrylate homopolymer with a polymerization degree k=100-200; the solid mass fraction of the organic-inorganic hybrid polymer hydrogel is 35±1%, and the thermal conductivity after film formation is 0.07W / (m·K).
[0099] The preparation method of the above organic-inorganic hybrid polymer hydrogel is:
[0100] Step 1) methyl orthosilicate, monomer A and monomer B are blended in a molar ratio of 1:1.5:1.5 to obtain a mixed solution No. 1, and stored in dry ice mixed with ethanol until the temperature of the mixed solution No. 1 drops below 0° C., maintaining the temperature, slowly adding methanol, and stirring at a low speed for 1 hour to obtain a solubilized mixed solution No. 1;
[0101] Step 2) blending monomer C, initiator, and deionized water to obtain a blend liquid No. 2, wherein the weight fractions of the components in the blend liquid No. 2 are: 40% by weight of monomer C, 4% by weight of initiator, stirring the blend liquid No. 2 at a low speed, and adjusting the pH value of the system to 7.5-9.0 using sodium hydroxide or ammonia water to obtain a pre-emulsified blend liquid No. 2;
[0102] Step 3) adjusting the temperature of the sol-gelled No. 1 blend to 45-55° C., and slowly adding the pre-emulsified No. 2 blend thereto, maintaining the temperature with low-speed stirring and condensing and refluxing, starting a free radical emulsion polymerization reaction, and starting gelation, and continuing for 6 hours until the pH value of the system rises to above 7.0, to obtain a No. 3 blend that has completed polymerization and gelation;
[0103] Step 4) dialyze the No. 3 blend at least 3 times, each dialysis time is 8 hours, and new dialysis fluid (i.e., deionized water) is replaced between two dialysis. After the dialysis is completed, 20% by weight of deionized water is added, and condensation reflux is carried out at 80-85° C. for about 2 hours to finally obtain an organic-inorganic hybrid polymer hydrogel.
[0104] A thermal insulation mid-coat for exterior walls comprises the following components in parts by weight: 15.0 parts by weight of modified hollow glass microspheres, 40.0 parts by weight of organic-inorganic hybrid polymer hydrogel, 15.0 parts by weight of pigments and fillers, 1.0 parts by weight of film-forming aids, 0.5 parts by weight of dispersants, 0.3 parts by weight of wetting agents, 0.5 parts by weight of defoaming agents, 1.2 parts by weight of antifreeze agents, 0.4 parts by weight of thickeners, 0.2 parts by weight of pH regulators, 0.7 parts by weight of bactericides and mildew inhibitors, and 15.2 parts by weight of deionized water.
[0105] The preparation method of the above-mentioned exterior wall thermal insulation mid-coat comprises the following steps:
[0106] Step S1: firstly add part of the thickener and half of the defoamer, all the film-forming aids, wetting agents, dispersants and pH regulators into deionized water, and disperse for 10-15 minutes at a peripheral linear speed of 10-15 m / s on a dispersion plate;
[0107] Step S2: adding all the modified hollow glass microspheres, film-forming silica aerogel slurry and pigments and fillers, increasing the speed of the dispersion disk, and dispersing for 15-20 minutes at a peripheral linear speed of 15-20 m / s;
[0108] Step S3: adding the remaining thickener, defoamer, antifreeze agent and bactericide and mildew preventer, and dispersing for 20-30 minutes at a peripheral linear speed of 10-15 m / s on the dispersion plate to obtain the exterior wall thermal insulation intermediate coating.
[0109] Example 3
[0110] An organic-inorganic hybrid polymer hydrogel has a structural formula as shown in formula (I), a chain length of a repeating unit A of m=700-800, a bridging polymer linking crosslinking points, a repeating unit B of propyl methacrylate homopolymer with a polymerization degree n=500-600, and a repeating unit C of vinyl methacrylate homopolymer with a polymerization degree k=200-300; the solid mass fraction of the organic-inorganic hybrid polymer hydrogel is 39±1%, and the thermal conductivity after film formation is 0.08W / (m·K).
[0111] The preparation method of the above organic-inorganic hybrid polymer hydrogel is:
[0112] Step 1) methyl orthosilicate, monomer A and monomer B are blended in a molar ratio of 1:2:2 to obtain a mixed solution No. 1, and stored in dry ice mixed with ethanol until the temperature of the mixed solution No. 1 drops below 0° C., maintaining the temperature, slowly adding methanol, and stirring at a low speed for 1 hour to obtain a solubilized mixed solution No. 1;
[0113] Step 2) blending monomer C, initiator, and deionized water to obtain a blend liquid No. 2, wherein the weight fractions of the components in the blend liquid No. 2 are: 50% by weight of monomer C, 5% by weight of initiator, stirring the blend liquid No. 2 at a low speed, and adjusting the pH value of the system to 7.5-9.0 using sodium hydroxide or ammonia water to obtain a pre-emulsified blend liquid No. 2;
[0114] Step 3) adjusting the temperature of the sol-gelled No. 1 blend to 45-55° C., and slowly adding the pre-emulsified No. 2 blend thereto, maintaining the temperature with low-speed stirring and condensing and refluxing, starting a free radical emulsion polymerization reaction, and starting gelation, and continuing for 6 hours until the pH value of the system rises to above 7.0, to obtain a No. 3 blend that has completed polymerization and gelation;
[0115] Step 4) dialyze the No. 3 blend at least 3 times, each dialysis time is 8 hours, and new dialysis fluid (i.e., deionized water) is replaced between two dialysis. After the dialysis is completed, 20% by weight of deionized water is added, and condensation reflux is carried out at 80-85° C. for about 2 hours to finally obtain an organic-inorganic hybrid polymer hydrogel.
[0116] A thermal insulation mid-coat for exterior walls comprises the following components in parts by weight: 12.0 parts by weight of modified hollow glass microspheres, 60.0 parts by weight of organic-inorganic hybrid polymer hydrogel, 15.0 parts by weight of pigments and fillers, 1.0 parts by weight of film-forming aids, 0.5 parts by weight of dispersants, 0.3 parts by weight of wetting agents, 0.5 parts by weight of defoaming agents, 1.2 parts by weight of antifreeze agents, 0.4 parts by weight of thickeners, 0.2 parts by weight of pH regulators, 0.7 parts by weight of bactericides and mildew inhibitors, and 8.2 parts by weight of deionized water.
[0117] The preparation method of the above-mentioned exterior wall thermal insulation mid-coat comprises the following steps:
[0118] Step S1: firstly add part of the thickener and half of the defoamer, all the film-forming aids, wetting agents, dispersants and pH regulators into deionized water, and disperse for 10-15 minutes at a peripheral linear speed of 10-15 m / s on a dispersion plate;
[0119] Step S2: adding all the modified hollow glass microspheres, film-forming silica aerogel slurry and pigments and fillers, increasing the speed of the dispersion disk, and dispersing for 15-20 minutes at a peripheral linear speed of 15-20 m / s;
[0120] Step S3: adding the remaining thickener, defoamer, antifreeze agent and bactericide and mildew preventer, and dispersing for 20-30 minutes at a peripheral linear speed of 10-15 m / s on the dispersion plate to obtain the exterior wall thermal insulation intermediate coating.
[0121] Table 1 Amount of each component used in the external wall insulation mid-coat paint of Examples 1 to 3 (parts by weight)
[0122]
[0123] Comparative Examples 1 to 3 provide exterior wall thermal insulation mid-coat paints. The preparation methods of the modified hollow glass microspheres and organic-inorganic hybrid polymer hydrogels used in these three comparative examples are the same as those in Example 1.
[0124] Comparative Example 1
[0125] The present comparative example provides an exterior wall thermal insulation mid-coat, which comprises the following components, based on the total weight of the coating: 18.0 parts by weight of unmodified hollow glass microspheres, 40.0 parts by weight of organic-inorganic hybrid polymer hydrogel, 15.0 parts by weight of pigments and fillers, 1.0 parts by weight of film-forming aids, 0.5 parts by weight of dispersants, 0.3 parts by weight of wetting agents, 0.5 parts by weight of defoaming agents, 1.2 parts by weight of antifreeze agents, 0.4 parts by weight of thickeners, 0.15 parts by weight of pH regulators, 0.7 parts by weight of bactericides and mildew inhibitors, and 25.2 parts by weight of deionized water.
[0126] The preparation method of the above-mentioned exterior wall thermal insulation mid-coat comprises the following steps:
[0127] 1) First add part of the thickener and half of the defoamer, all the film-forming aids, wetting agents, dispersants and pH adjusters into deionized water, and disperse for 10-15 minutes at a peripheral linear speed of 10-15 m / s on the dispersion plate;
[0128] 2) Add all the unmodified hollow glass microspheres, organic-inorganic hybrid polymer hydrogel and pigments and fillers, increase the speed of the dispersion disk, and disperse for 15-20 minutes at a peripheral linear speed of 15-20 m / s;
[0129] 3) adding the remaining thickener, defoamer, antifreeze agent and bactericide and mildew preventer, and dispersing for 20-30 minutes at a peripheral linear speed of 10-15 m / s on the dispersion plate to obtain the exterior wall thermal insulation intermediate coating.
[0130] Comparative Example 2
[0131] The present comparative example provides an exterior wall thermal insulation mid-coat, which comprises the following components, based on the total weight of the coating: 18.0 parts by weight of modified hollow glass microspheres, 5.0 parts by weight of silica aerogel powder, 32.0 parts by weight of acrylic emulsion, 15.0 parts by weight of pigment and filler, 1.0 parts by weight of film-forming aid, 0.5 parts by weight of dispersant, 0.3 parts by weight of wetting agent, 0.5 parts by weight of defoaming agent, 1.2 parts by weight of antifreeze agent, 0.4 parts by weight of thickener, 0.15 parts by weight of pH adjuster, 0.7 parts by weight of bactericidal and mildewproof agent, and 25.25 parts by weight of deionized water.
[0132] The preparation method of the above-mentioned exterior wall thermal insulation mid-coat comprises the following steps:
[0133] 1) First add part of the thickener and half of the defoamer, all the film-forming aids, wetting agents, dispersants and pH adjusters into deionized water, and disperse for 10-15 minutes at a peripheral linear speed of 10-15 m / s on the dispersion plate;
[0134] 2) Add all the modified hollow glass microspheres, silica aerogel powder and pigments and fillers, increase the speed of the dispersion disk, and disperse for 15-20 minutes at a peripheral linear speed of 15-20 m / s;
[0135] 3) adding acrylic emulsion, remaining thickener, defoamer, antifreeze agent and bactericide and mildewproof agent, dispersing for 20-30 minutes at a peripheral linear speed of 10-15 m / s on a dispersion plate, to obtain the exterior wall thermal insulation intermediate coating.
[0136] Comparative Example 3
[0137] The present comparative example provides an exterior wall thermal insulation intermediate coating, which comprises the following components, based on the total weight of the coating: 20.0 parts by weight of acrylic emulsion, 37.0 parts by weight of pigment and filler, 1.0 parts by weight of film-forming aid, 0.5 parts by weight of dispersant, 0.3 parts by weight of wetting agent, 0.5 parts by weight of defoaming agent, 1.2 parts by weight of antifreeze agent, 0.4 parts by weight of thickener, 0.15 parts by weight of pH adjuster, 0.7 parts by weight of bactericidal and mildewproof agent, and 38.2 parts by weight of deionized water.
[0138] The preparation method of the above-mentioned exterior wall thermal insulation mid-coat comprises the following steps:
[0139] 1) First add part of the thickener and half of the defoamer, all the film-forming aids, wetting agents, dispersants and pH adjusters into deionized water, and disperse for 10-15 minutes at a peripheral linear speed of 10-15 m / s on the dispersion plate;
[0140] 2) Add all the pigments and fillers, increase the speed of the dispersion disk, and disperse for 15-20 minutes at a peripheral linear speed of 15-20 m / s;
[0141] 3) adding the emulsion, the remaining thickener, the defoamer, the antifreeze agent and the bactericide and mildew preventer, and dispersing for 20-30 minutes at a peripheral linear speed of 10-15 m / s on the dispersion plate to obtain the exterior wall thermal insulation intermediate coating.
[0142] Test Case
[0143] The present invention tests the intermediate coatings of Examples 1 to 3 and Comparative Examples 1 to 2, and the test items are: thermal conductivity, bonding strength, low temperature flexibility, initial water resistance, low temperature and high humidity film forming property and storage stability.
[0144] Thermal conductivity, bonding strength and low temperature flexibility are carried out in accordance with the provisions of GB 25261-2018. The initial water resistance test method is as follows: prepare a 2mm thick paint film on an iron plate, and after curing for 16 hours under standard conditions, place the paint film vertically in deionized water and soak it for 24 hours to observe whether there is bulging or other phenomena.
[0145] The low-temperature and high-humidity film-forming property test method is as follows: prepare a 2 mm thick paint film on an iron plate, immediately maintain it in an environment of 5°C and 90% relative humidity for 24 hours, and observe whether the paint film is completely dry.
[0146] Storage stability includes room temperature storage stability, low temperature storage stability and hot storage stability. The test method is as follows: fill a 5L sealed can with thermal insulation middle layer paint, and let it stand for 30 days at room temperature (25°C), low temperature (5°C) and high temperature (55°C). After taking out the sample, observe whether it is stratified and whether it is easy to mix evenly after stirring and presents a uniform slurry state.
[0147] Table 2 Performance test results of Examples 1 to 3 and Comparative Examples 1 to 3
[0148]
[0149] It can be seen from the test results of the embodiments and comparative examples shown in Table 2 that the performance of the heat-insulating mid-coat prepared in Examples 1 to 3 meets the basic performance requirements of the heat-insulating mid-coat in GB / T 25261 "Reflective Heat-Insulating Coatings for Buildings", and the storage stability of these three mid-coat paints is good. However, in the above main performances, some items of Comparative Examples 1 to 2 are not as good as those of the embodiments. Comparative Example 1 uses unmodified hollow glass microspheres, which have slightly poor compatibility with acrylic emulsion and poor storage stability of the system. After storage, the lightweight glass microspheres will float on the surface of the coating, with poor appearance and difficult to stir. Comparative Example 2 uses ordinary silica aerogel powder and acrylic emulsion instead of the organic-inorganic hybrid polymer hydrogel of the present invention. The aerogel powder itself cannot form a film and will absorb a large amount of polymer emulsion, causing the paint film to be too brittle after curing, and the coating will become dry and hard after being stored for a period of time and cannot be used. Comparative Example 3 uses pigments and fillers to replace functional components. Its basic properties are close to those of ordinary latex paints, and its thermal conductivity is only 2.50 W / (m·K), which does not have any thermal insulation performance.
[0150] The above test results show that the thermal insulation middle layer paint prepared by the present invention has the advantages of stable storage, low thermal conductivity and high bonding strength.
[0151] The above description is only a preferred embodiment of the present invention and does not constitute any other form of limitation to the present invention. Any modification or equivalent change made based on the technical essence of the present invention still falls within the scope of protection required by the present invention.
Claims
1. An organic-inorganic hybrid polymer hydrogel, characterized in that: The solid mass fraction of the organic-inorganic hybrid polymer hydrogel is 33±1%, and the thermal conductivity after film formation is 0.06W / (m·K); The preparation method of the organic-inorganic hybrid polymer hydrogel is: Step 1) methyl orthosilicate, monomer A and monomer B are blended in a molar ratio of 1:1:1 to obtain a mixed liquid No. 1, and stored in dry ice mixed with ethanol until the temperature of the mixed liquid No. 1 drops below 0° C., maintaining the temperature, slowly adding methanol, and stirring at a low speed for 1 hour to obtain a solubilized mixed liquid No. 1; Step 2) Blending monomer C, initiator and deionized water to obtain blend liquid No. 2, wherein the weight fractions of the components in blend liquid No. 2 are: 30% by weight of monomer C, 2% by weight of initiator, stirring blend liquid No. 2 at a low speed, and adjusting the pH value of the system to 7.5-9.0 with sodium hydroxide or ammonia water to obtain pre-emulsified blend liquid No. 2; Step 3) adjusting the temperature of the sol-gelled No. 1 blend to 45-55° C., and slowly adding the pre-emulsified No. 2 blend thereto, maintaining the temperature with low-speed stirring and condensing and refluxing, starting a free radical emulsion polymerization reaction, and starting gelation, and continuing for 6 hours until the pH value of the system rises to above 7.0, to obtain a No. 3 blend that has completed polymerization and gelation; Step 4) dialyzing the No. 3 blend at least 3 times, each dialysis time is 8 hours, and a new dialysate is replaced between two dialysis. After the dialysis is completed, 20% by weight of deionized water is added, and condensed and refluxed at 80-85° C. for 2 hours to finally obtain the organic-inorganic hybrid polymer hydrogel; Wherein, monomer A is 1,6-bistrimethoxysilylhexane; Monomer B is 3-(trimethoxysilyl)propyl methacrylate; Monomer C is vinyl methacrylate; The initiator is azobisisobutyronitrile.
2. An organic-inorganic hybrid polymer hydrogel, characterized in that: The solid mass fraction of the organic-inorganic hybrid polymer hydrogel is 35±1%, and the thermal conductivity after film formation is 0.07 W / (m·K); The preparation method of the organic-inorganic hybrid polymer hydrogel is: Step 1) methyl orthosilicate, monomer A and monomer B are blended in a molar ratio of 1:1.5:1.5 to obtain a mixed solution No. 1, and stored in dry ice mixed with ethanol until the temperature of the mixed solution No. 1 drops below 0° C., maintaining the temperature, slowly adding methanol, and stirring at a low speed for 1 hour to obtain a solubilized mixed solution No. 1; Step 2) blending monomer C, initiator, and deionized water to obtain a blend liquid No. 2, wherein the weight fractions of the components in the blend liquid No. 2 are: 40% by weight of monomer C, 4% by weight of initiator, stirring the blend liquid No. 2 at a low speed, and adjusting the pH value of the system to 7.5-9.0 using sodium hydroxide or ammonia water to obtain a pre-emulsified blend liquid No. 2; Step 3) adjusting the temperature of the sol-gelled No. 1 blend to 45-55° C., and slowly adding the pre-emulsified No. 2 blend thereto, maintaining the temperature with low-speed stirring and condensing and refluxing, starting a free radical emulsion polymerization reaction, and starting gelation, and continuing for 6 hours until the pH value of the system rises to above 7.0, to obtain a No. 3 blend that has completed polymerization and gelation; Step 4) dialyzing the No. 3 blend at least 3 times, each dialysis time is 8 hours, and a new dialysate is replaced between two dialysis. After the dialysis is completed, 20% by weight of deionized water is added, and condensed and refluxed at 80-85° C. for 2 hours to finally obtain the organic-inorganic hybrid polymer hydrogel; Wherein, monomer A is 1,6-bistrimethoxysilylhexane; Monomer B is 3-(trimethoxysilyl)propyl methacrylate; Monomer C is vinyl methacrylate; The initiator is azobisisobutyronitrile.
3. An organic-inorganic hybrid polymer hydrogel, characterized in that: The solid mass fraction of the organic-inorganic hybrid polymer hydrogel is 39±1%, and the thermal conductivity after film formation is 0.08 W / (m·K); The preparation method of the organic-inorganic hybrid polymer hydrogel is: Step 1) methyl orthosilicate, monomer A and monomer B are blended in a molar ratio of 1:2:2 to obtain a mixed solution No. 1, and stored in dry ice mixed with ethanol until the temperature of the mixed solution No. 1 drops below 0° C., maintaining the temperature, slowly adding methanol, and stirring at a low speed for 1 hour to obtain a solubilized mixed solution No. 1; Step 2) blending monomer C, initiator, and deionized water to obtain a blend liquid No. 2, wherein the weight fractions of the components in the blend liquid No. 2 are: 50% by weight of monomer C, 5% by weight of initiator, stirring the blend liquid No. 2 at a low speed, and adjusting the pH value of the system to 7.5-9.0 using sodium hydroxide or ammonia water to obtain a pre-emulsified blend liquid No. 2; Step 3) adjusting the temperature of the sol-gelled No. 1 blend to 45-55° C., and slowly adding the pre-emulsified No. 2 blend thereto, maintaining the temperature with low-speed stirring and condensing and refluxing, starting a free radical emulsion polymerization reaction, and starting gelation, and continuing for 6 hours until the pH value of the system rises to above 7.0, to obtain a No. 3 blend that has completed polymerization and gelation; Step 4) dialyzing the No. 3 blend at least 3 times, each dialysis time is 8 hours, and a new dialysate is replaced between two dialysis. After the dialysis is completed, 20% by weight of deionized water is added, and condensed and refluxed at 80-85° C. for 2 hours to finally obtain the organic-inorganic hybrid polymer hydrogel; Wherein, monomer A is 1,6-bistrimethoxysilylhexane; Monomer B is 3-(trimethoxysilyl)propyl methacrylate; Monomer C is vinyl methacrylate; The initiator is azobisisobutyronitrile.
4. An exterior wall thermal insulation mid-coat paint, characterized in that: The exterior wall thermal insulation mid-coat paint comprises the following components in parts by weight: Modified hollow glass microspheres 8.0-20.0 parts by weight, 30.0-70.0 parts by weight of the organic-inorganic hybrid polymer hydrogel according to any one of claims 1 to 3, Pigments and fillers 10.0-30.0 parts by weight; 0.5-2.0 parts by weight of film-forming aid; Dispersant 0.1-1.0 parts by weight; Wetting agent 0.1-1.0 parts by weight; Defoaming agent 0.1-1.0 parts by weight; Antifreeze agent 0.5-2.0 parts by weight; Thickener 0.1-1.0 parts by weight; 0.1-1.0 parts by weight of bactericidal and mildew-proof agent; 0.1-1.0 parts by weight of a pH adjuster; and Deionized water 20.0-40.0 parts by weight.
5. The exterior wall thermal insulation mid-coat paint according to claim 4, characterized in that: The modified hollow glass microspheres are hollow glass microspheres that have been surface treated with a silane coupling agent, have a particle size of 10-150 μm, and a bulk density of 0.14±0.03 g / cm 3 , floating rate ≥99%, bearing strength ≥6.8MPa, silica content>99%, wall thickness between 0.8 and 1.5um, and sphericity greater than 0.
9.
6. The exterior wall thermal insulation mid-coat paint according to claim 5, characterized in that: The silane coupling agent is at least one of 3-aminopropyltriethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane and a titanate coupling agent.
7. A method for preparing the exterior wall thermal insulation mid-coat according to any one of claims 4 to 6, characterized in that: The preparation method comprises the following steps: Step S1: firstly add part of the thickener and half of the defoamer, all the film-forming aids, wetting agents, dispersants and pH regulators into deionized water, and disperse for 10-15 minutes at a peripheral linear speed of 10-15 m / s on a dispersion plate; Step S2: adding all the modified hollow glass microspheres, organic-inorganic hybrid polymer hydrogel and pigments and fillers, increasing the speed of the dispersion disk, and dispersing for 15-20 minutes at a peripheral linear speed of 15-20 m / s; Step S3: adding the remaining thickener, defoamer, antifreeze agent and bactericide and mildew preventer, and dispersing for 20-30 minutes at a peripheral linear speed of 10-15 m / s on the dispersion plate to obtain the exterior wall thermal insulation intermediate coating.
Citation Information
Patent Citations
Open bottom box culvert
CA2530850A1
Devices, systems, and methods for delivering fluid to tissue
CA2768027A1
Preparation method and application of water-soluble SiO2 aerogel exterior wall reflective heat insulation coating
CN109913007B
Acrylic acid-potassium silicate copolymer emulsion, preparation and application thereof, breathable flame-retardant weather-resistant exterior wall inorganic coating and preparation thereof
CN115124666A
An aqueous polymer dispersion containing copolymerisate obtained by free radical polymerization useful for coatings having high corrosion and condensation resistance
DE10236395A1